A Comparison of Outcomes for Spinal Trauma Patients at Level I and Level II Centers. Issue 4 (May 2021) - Baron, Rebecca B.; Neifert, Sean N.; Martini, Michael L.; Maragkos, George A.; McNeill, Ian T.; Lamb, Colin; Rasouli, Jonathan J.; Caridi, John M.
Abstract : Study Design: Retrospective analysis of a national database. Objective: To characterize the spine trauma population, describe trauma center (TC) resources, and compare rates of outcomes between the American College of Surgeons (ACS) level I and level II centers. Summary of Background Data: Each year, thousands of patients are treated for spinal trauma in the United States. Although prior analyses have explored postsurgical outcomes for patients with trauma, no study has evaluated these metrics for spinal trauma at level I and level II TCs. Materials and Methods: The ACS Trauma Quality Improvement Program was queried for all spinal trauma cases between 2013 and 2015, excluding polytrauma cases, patients discharged within 24 hours, data from TCs without a designated level, and patients transferred for treatment. Results: Although there were similar rates of severe spine traumas (Abbreviated Injury Scale≥3) at ACS level I and level II centers ( P =0.7), a greater proportion of level I patients required mechanical ventilation upon emergency department arrival ( P =0.0002). Patients at level I centers suffered from higher rates of infectious complications, including severe sepsis (0.58% vs. 0.31%, P =0.02) and urinary tract infections (3.26% vs. 2.34%, P =0.0009). Intensive care unit time (1.90 vs. 1.65 days, P =0.005) and overall length of stay (8.37 days vs. 7.44 days, P <0.0001) was higher at level I TCs. Multivariate regression revealed higher adjusted overall complication rates at level II centers (odds ratio, 1.15, 95% confidence interval, 1.06–1.24; P <0.001), but no difference in mortality (odds ratio, 1.18; 95% confidence interval, 0.92–1.52; P >0.10). Conclusions: ACS level I TCs possess larger surgical staff and are more likely to be academic centers. Patients treated at level I centers experience fewer overall complications but have a greater incidence of infectious complications. Mortality rates are not statistically different.